2016
DOI: 10.1039/c6tc01378c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and thermoelectric properties of superconducting (BEDT-TTF)2I3nanoparticles

Abstract: (BEDT-TTF)2I3 nanoparticles of 2–6 nm have been isolated, and they exhibit a superconducting behaviour and encouraging thermoelectric properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…From the 1990s, thin films [2] and nanorod arrays [3] of -(BEDT-TTF) 2 Cu(NCS) 2 have also been reported. Some of us have shown that roughly spherical nanoparticles of molecule-based conductors could be prepared either by a chemical or an electrochemical route by adding to the solution a growth controlling agent, such as an amphiphilic molecule, an ionic liquid or a long alkyl-chain quaternary ammonium salt [4][5][6][7][8]. We have already described the synthesis of nanoparticles of -(BEDT-TTF) 2 Cu(NCS) 2 by a chemical or an electrochemical route.…”
Section: Introductionmentioning
confidence: 99%
“…From the 1990s, thin films [2] and nanorod arrays [3] of -(BEDT-TTF) 2 Cu(NCS) 2 have also been reported. Some of us have shown that roughly spherical nanoparticles of molecule-based conductors could be prepared either by a chemical or an electrochemical route by adding to the solution a growth controlling agent, such as an amphiphilic molecule, an ionic liquid or a long alkyl-chain quaternary ammonium salt [4][5][6][7][8]. We have already described the synthesis of nanoparticles of -(BEDT-TTF) 2 Cu(NCS) 2 by a chemical or an electrochemical route.…”
Section: Introductionmentioning
confidence: 99%
“…The growth controlling agents evaluated in this study, namely, OATM and BIBS, prevented the preparation of Per 2 [Au(mnt) 2 ] as micro-sized crystals. Irregularly shaped nanocrystals are grown in the presence Moreover, the thermal conductivity λ is very low for organic-based conductors as nanoparticles [13]. As the thermoelectric efficiency of a material is evaluated by its figure of merit ZT in which S 2 is in the numerator and λ in the denominator, Per 2 [Au(mnt) 2 ] nanoparticles described in this paper could be interesting as one of the components for organic-based thermoelectric devices.…”
Section: Resultsmentioning
confidence: 99%
“…( Figure 5). [19] Nanoparticles were larger, 85 nm and 40 nm, when using dodecylamine and hexadecylamine, respectively. The efficiency of 1-octanamine-N-(2-thienylmethylene) can be explained by possible π-π and S•••S van-der Waals interactions, in addition to the long chain protection.…”
Section: Chemical Methodsmentioning
confidence: 95%